Taxonomia e paleoecologia de asterozoa da formação Rio Bonito (Taió-SC, Brasil) - Klein, Gabriel (Universidade do Vale do Rio dos Sinos, 2021)
In the Paraná Basin an uncommon occurrence is record in the marine beds from Lower Permian Rio Bonito Formation. These sedimentary strata are compound by muddy to coarse sand bioturbated beds interpreted as deposition in shallow shelf and marginal marine environments. In the order to do a taxonomic revision, intending a new classification in a generic level is proposed. Additionally, taphonomical and paleoecological approach is presented. Eighteen specimens housed in the Museu de História Geológica do Rio Grande do Sul (MHGeo – Unisinos) was handled to do the taxonomic revision. The taxonomy pointed out morphologic features similar to modern genus Astropecten Gray, 1840. This is the first occurrence to Astropecten in Paleozoic deposits representing the oldest record of the genus. Taphonomically analysis revel an obruption condition to genesis of the fossiliferous deposits. However, a deepest revision is necessary yet.
Keywords: Estrelas-do-mar; Astropecten; Permiano Inferior; Invertebrados fosseis; Sea-stars; Astropecten; Lower Permian; Fossil invertebrates